Going for Broke : Insolvency Tools to Support Cross-Border Asset Recovery in Corruption Cases - Brun, Jean-Pierre (Washington, DC: World Bank, 2019)
The cost of official corruption is high: it degrades public trust, impedes economic development, and undermines the rule of law. Countries around the world are increasingly using asset recovery measures to pursue justice in official corruption cases and restore funds to public use. Successful application of bankruptcy or insolvency law can make or break a corruption case. Going for Broke: Insolvency Tools to Support Cross-Border Asset Recovery in Corruption Cases is intended as a guidebook for asset recovery practitioners for the use of bankruptcy proceedings in their work. It is offered as a complement to our prior texts: Public Wrongs, Private Actions and Asset Recovery Handbook. Going for Broke offers practical advice to inform insolvency representatives, law enforcement officials, policy makers, and those entrusted with recovering their nations’ stolen assets about the ways in which insolvency can be effectively be employed—either to complement an existing civil or criminal asset recovery action or as a stand-alone procedure for recovery. It may also serve as a quick reference for other practitioners, including auditors, accountants, and others who deal with corruption and asset recovery.